Pengelolaan TPA Bantar Gebang dalam Perspektif Hukum Lingkungan: Penerapan Prinsip Perlindungan dan Penegakan Hukum Lingkungan Hidup - Pariwusiana Anwar; Deizan Azriel Drahmasyfa; Aisyah Nurmala Hidayati; Laila Nurfadilah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The management of the Bantar Gebang Final Disposal Site (TPA) faces structural challenges related to capacity limitations, environmental pollution, and the fulfillment of the communityâ€™s right to a good and healthy environment. This study analyzes the application of environmental law enforcement principles as regulated in Law Number 32 of 2009, focusing on the principles of precaution, pollution prevention, the polluter pays principle, sustainability, and community participation in landfill management practices. The research findings indicate that although technical approaches such as sanitary landfills and the development of waste-to-energy (PLTSa) facilities have been implemented, gaps in implementation persist due to the high volume of waste, weak supervision, and the dominance of an end-of-pipe disposal approach without adequate upstream waste reduction strategies. Legal instruments such as Environmental Impact Assessments (AMDAL), environmental permitting, and administrative sanctions tend to be reactive in nature and have not fully ensured the imposition of restoration costs on polluters. Furthermore, community participation remains limited due to the lack of dialogue mechanisms and management accountability. This study recommends strengthening law enforcement through stricter supervision, enhancing public participation mechanisms, developing a collaborative governance model across regions between DKI Jakarta and the City of Bekasi, and integrating upstream waste reduction programs with social protection for waste pickers.Â